1990
DOI: 10.1149/1.2086931
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Model for Wet Cleaning of Deep Trenches

Abstract: Wet cleaning of deep trenches, 4 ~m deep and 0.5 ~m wide, was studied using a two-dimensional wet cleaning simulation including both flow and diffusion effects. It has turned out that the diffusion effect is a dominant factor during wet cleaning. When the flow velocity of the rinse water increases, the rate at which solution in trenches is replaced becomes higher. In our simulation, the solution in the deep trench is diluted to 1 ppm by rinse water within several seconds. This result shows that deep trenches w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is described by the Pascal equation = 2-y cos 0/w [11 where p = p, -P1qud is the pressure difference across the interface, y is the surface tension, 0 is the contact angle, and w is the gap width. This is described by the Pascal equation = 2-y cos 0/w [11 where p = p, -P1qud is the pressure difference across the interface, y is the surface tension, 0 is the contact angle, and w is the gap width.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is described by the Pascal equation = 2-y cos 0/w [11 where p = p, -P1qud is the pressure difference across the interface, y is the surface tension, 0 is the contact angle, and w is the gap width. This is described by the Pascal equation = 2-y cos 0/w [11 where p = p, -P1qud is the pressure difference across the interface, y is the surface tension, 0 is the contact angle, and w is the gap width.…”
Section: Resultsmentioning
confidence: 99%
“…Wetting-The driving force of wetting is a pressure gradient that arises from the hydrophilic nature of the Si02 surface. This is described by the Pascal equation = 2-y cos 0/w [11 where p = p, -P1qud is the pressure difference across the interface, y is the surface tension, 0 is the contact angle, and w is the gap width. Analysis of this equation shows that for a 0.5 p.m Si02 feature, the wetting time is less than 1000 ms.1° From contact angle measurements, we have confirmed that the Si02 surface becomes more hydrophilic after the sequence of oxygen plasma and SPM treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas some chemicals (i.e. HF) exhibit an excellent wetting [6] some other ones (i.e. SC1) show poor wetting [7].…”
Section: Structures Wetting By Wet Chemicalsmentioning
confidence: 99%
“…Although the substrate of interest is nonplanar, the flat plate model is a valid approximation because the flow is approximately equal to zero within the features as well. 14 Because the flow profile is nearly unidirectional, diffusion dominates in the y direction ͑in the limit of tightly packed features, otherwise radial diffusion oc-curs͒, and convection dominates in the x direction. Therefore, Eq.…”
Section: Complete Wetting Through Gas Transportmentioning
confidence: 99%